IMPLEMENTATION IN COMPUTER NETWORKS INTERNET CAFES (WARNET) "XYZ" - Achmad Suhendra; Yuce Yuliani, SKom, MM (Jurnal Sistem Informasi, 2000)
Computer network is  a combination of various communication equipment and computers that are connected to one another via a communications medium so that all network users can communicate with each other electronically. Internet gives an opportunity for users worldwide to communicate and will share information resources. Computer network is just a medium that carries information, the efficiency of the Internet lies in the information itself is oriented to human. As a user of the Internet we can communicate with other users simply by sending and receiving e-mail or held talks in realtime with friends around the world. Therefore, the authors try to give some idea that the Internet network requires sophisticated tools to make the Internet network as a computer network implementation. And the author also provides information on the actual LAN is connected to the Internet at all because it includes a LAN equipment required by the Internet in addition to other equipment.